2012
DOI: 10.1186/1475-2875-11-402
|View full text |Cite
|
Sign up to set email alerts
|

Anti-malarial drug safety information obtained through routine monitoring in a rural district of South-Western Senegal

Abstract: BackgroundKnowing the safety profile of anti-malarial treatments in routine use is essential; millions of patients receive now artemisinin combination therapy (ACT) annually, but the return on information through current systems is as yet inadequate. Cohort event monitoring (CEM) is a WHO (World Health Organization)-recommended practice; testing its performance and feasibility in routine practice in malaria-endemic is important.MethodsA nine-year CEM-based study of the safety of artesunate-amodiaquine (ASAQ) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…However, the study population was different from that of this study, being exclusively urban and predominantly adult (66.1% aged ≥13 years) and the anti-malarial treatment was not restricted to a specific anti-malarial medicine (43% of treatments were free or fixed combinations of AS and AQ, all brands considered). In a CEM study of patients treated with AS and AQ combinations (various free or fixed formulations over time) in rural Senegal, performed between 2001 and 2009 [24], patients were required to return to the HC every day for the 4 days following start of treatment and again after 4 weeks, where data on AEs were collected using a structured questionnaire. The rate of AEs reporting in the study (12%) is close to that observed in the present study in Côte d’Ivoire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the study population was different from that of this study, being exclusively urban and predominantly adult (66.1% aged ≥13 years) and the anti-malarial treatment was not restricted to a specific anti-malarial medicine (43% of treatments were free or fixed combinations of AS and AQ, all brands considered). In a CEM study of patients treated with AS and AQ combinations (various free or fixed formulations over time) in rural Senegal, performed between 2001 and 2009 [24], patients were required to return to the HC every day for the 4 days following start of treatment and again after 4 weeks, where data on AEs were collected using a structured questionnaire. The rate of AEs reporting in the study (12%) is close to that observed in the present study in Côte d’Ivoire.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of three characterized cases in this study prompted the Marketing Authorization Holder for ASAQ Winthrop ® to carry out a comprehensive assessment of the association of extrapyramidal disorders with ASAQ Winthrop ® or other anti-malarial drugs in 2012, which led to extrapyramidal disorders being listed as adverse drug reactions in the prescribing information for ASAQ Winthrop ® . Around the same time, an analysis was published of some of the earlier pharmacovigilance reports documented in the WHO global pharmacovigilance database (VigiBase™) [29], and there have been further subsequent reports of extrapyramidal symptoms in patients taking artemisinin and amodiaquine combinations elsewhere in Africa [23, 24, 30]. …”
Section: Discussionmentioning
confidence: 99%
“…Practical handbooks have been published by the WHO on how to conduct CEM in public health programmes for malaria, HIV/AIDS and tuberculosis [5–7]. Several CEM programmes have published their results from monitoring selected ACTs [1013], and one CEM programme has recently published preliminary results from monitoring antiretrovirals [14]. Related publications identify challenges for implementing pharmacovigilance in resource-constrained settings [15] and propose strategies to complement spontaneous reporting for monitoring the safety of medicines in public health programmes [7].…”
Section: Introductionmentioning
confidence: 99%
“…Amodiaquine-associated asthenia is a complaint of some users of amodiaquine and amodiaquine containing ACTs. In 2012, Brasuer et al reported an incidence of 17% of asthenia in 1,380 subjects who received amodiaquine-artesunate combination therapies [13]. Reports from Nigeria put the frequency between 5% and 36% with a lower incidence reported in children [12,14].…”
Section: Epidemiologymentioning
confidence: 99%